(untitled) - Dockery, Michael (Cambridge, 1999)
Behaviour describes animal and human behaviour, including environmental influence, behavioural development, courtship and social interaction. It covers all the material required for the study of behaviour at A-level, whilst at the same time providing an accessible and informative introduction to the fascinating science of behaviour.
Keywords: Animal behavior,Hành vi động vật